Towards emplaced understandings of risk: How caregivers of children with asthma identify and manage asthma-related risk across different places. (May 2022) - Ruiz, Sienna; Waters, Erika A.; Maki, Julia; Fedele, David A.; Pogge, Gabrielle; Shepperd, James A.; Hunleth, Jean
Abstract: In the United States, pediatric asthma is distributed geographically across lines of racialized segregation. We draw on emplacement, or the theory that embodied experiences and the material world are mutually informed, to situate such geographic trends within the narratives of 41 caregivers of children with asthma. Results suggest that caregivers identified and managed asthma-related risk with regard to the relational and structural conditions of three categories of locations: (1) houses, (2) neighborhoods, and (3) schools and other childhood institutions. Within each type of location, caregivers used emplaced knowledge and emplaced caregiving tactics to respond to asthma-related risk. Based on our findings, we identify critical intervention topics that are consistent with families' everyday lived experiences of place. Highlights: Caregivers understood risks to their child's asthma according to the places their family occupied in their day-to-day lives. Understandings of asthma-related risk varied across houses, neighborhoods, and schools and other childhood institutions. Caregivers used emplaced knowledge and caregiving tactics to identify and manage asthma-related risks in these places. Relational and structural conditions that families encountered in each place influenced their emplaced caregiving tactics. Emplaced understandings of asthma-related risk can inform interventions that match families' lived experiences of place.